Mattei Dogan y John D. Kasarda (comps.). The metropolis era. [Newbury Park, Calif.] : Sage Publications, 1987. 2 vols. - Muñoz Contreras, María Elena (El Colegio de México A.C., 1988)
MATTEI, DOGAN y JOHN D. KASARDA (comps.), The Metrópolis Era, Sage Publications, 1987.